Replacement name for the Genus Halticidea Reuter, 1901 and the subfamily Halticinae Kirkaldy, 1902 of Miridae (Insecta, Hemiptera). - Kiyak, Suat (Contributions to Entomology = Beiträge zur Entomologie, 1995)
A replacement name, Barbarosia (nom. nov.) is proposed for the genus Halticidea Reuter, 1901 in the family Miridae. It is a junior subjective homonym of Halticidea Horn 1893, according to article 53b of the Zoological Code. The subfamily Halticinae Kirkaldy, 1902 is a junior synonym for Labopinae Reuter, 1883. Nomenclatural Acts Barbarosia Kiyak, 1995 (Miridae), nom. n. pro Halticidea Reuter, 1901, nec Horn, 1893 Halticinae Kirkaldy, 1902 (Miridae), syn. n. of Labopinae Reuter, 1883 Labopinae Reuter, 1883 (Miridae), stat. n. hitherto a synonym of subfam. Halticinae Kirkaldy, 1902